Design of risk assessment and classification strategy using concentrated numeric statistic matrix and entropy method - A Nurhayati; A Gautama (IPTEK Journal of Proceedings Series, 2018)
The construction project is a dynamic and risky field. Risks can have an effect on productivity, quality and cost limits of the project. Risk management is crucial for any construction project to avoid loss of cost, quality and time. This research was conducted at PT. XYZ. Risk identification is done through field survey and stakeholder interviews. There are 73 identified risks that are classified into 7 types of risks. Questionnaires were distributed to experts for probability and impact data. Calculation of probability average value and the risk impact are being done by concentrated numeric statistic matrix (CNSM) method. The final step in CNSM is the data consistency test using G reliability test. While the division of risk category uses entropy method. The benefits of combining these two methods are the assessment and classification of risk can be more accurate. CNSM will calculate the highest risk from all of the 73 identified risks. While entropy method will find the highest risk from the 7 risks type. From the result of the 2 methods, we can crosscheck to find the highest identified risk in the highest risk group type. The result shows that the risk of weather variability is the highest one.